KAJIAN EFEKTIFITAS KAYU APU (Pistia stratiotes L.) DALAM MEREDUKSI N-TOTAL SEBAGAI UPAYA PERBAIKAN KUALITAS LIMBAH CAIR INDUSTRI TAHU - Irma Yuni; Wahyu Lestari; Yelmida ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
One of wastes that has high N-total is tofu liquid waste. Biologically waste disposal can be done by phytoremediation using Pistia stratiotes L. The purposes of this research were to test the growth ability of P. stratiotes in tofu liquid waste and to test its ability in accumulating N-total. The research used Random Device Complete with variation of tofu liquid waste concentrations i.e 20, 40, 60, 80, 100 %, and 0 % for control. The observed parameters consisted of fresh weight and the growth progress of P. stratiotes, and the analysis of N-total. The data was analyzed using ANOVA and followed by the DNMRT test at the level of 5 % . The result showed the decrease of fresh weight and growth rate significantly, in the concentration of 20 % ( 20,90 g and 7,07 g/ day). The analysis of N-total in final waste was significantly different in each treatment, while the content of N-total in plant was not different in each treatment, but only different with control. The decrease of plant growth and the increase of N-total content in final waste indicated that P. stratiotes was not effective to overcome the environmental contamination caused by industrial tofu liquid waste.